Nephelometer Sensitivities for the Determination of PM2.5 Mass Concentration in Ambient and Indoor Air - Dimitra Karali; Glykeria Loupa; Spyridon Rapsomanikis (Aerosol and Air Quality Research)
Abstract Simple algorithms are presented for the relationships between the gravimetrically measured PM2.5 mass concentration and a nephelometer particle scattering coefficient, for three different environments: two outdoor locations (an urban and a suburban) and one indoors. With these algorithms, the aerosol light scattering coefficients of the nephelometer (provided on line with a time step of seconds) can be related to PM2.5 mass concentrations. The effect of the relative humidity on the nephelometer readings was also evaluated with two models. In the last two campaigns (in the suburbs of the city and in a laboratory), a drying device before the aerosol entrance to the nephelometer was used, a Nafion™ dryer. In the indoor environment, the two methods (gravimetry and nephelometry) were compared with the readings of an aerosol light scattering spectrometer, which provided PM2.5 volume concentrations and thus it was possible to calculate the PM2.5 density indoors.